2008
DOI: 10.1103/physrevlett.100.156101
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interaction Anisotropy in the Formation and Stability of Molecular Templates

Abstract: Surface templating via self-assembly of hydrogen-bonded molecular networks is a rapidly developing bottom-up approach in nanotechnology. Using the melamine-PTCDI molecular system as an example we show theoretically that the network stability in the parameter space of temperature versus molecular coupling anisotropy is highly restricted. Our kinetic Monte Carlo simulations predict a structural stability diagram that contains domains of stability of an open honeycomb network, a compact phase, and a high-temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 31 publications
1
66
0
Order By: Relevance
“…Thus, although the rational design of molecules for biological and pharmaceutical applications is rather well established, only few works predict the complete self-assembly of soft materials using computational tools. 30,31,60,61 Experimental observations presented in this work for small work reflects not only self-similarity but also that the dendritic assembly occurs through a diffusion limited aggregation mechanism onto a plane (i.e. the surface substrate).…”
Section: Fractal Analysis Of Fmoc-ffff-ofm Dendritic Microarchitecturesmentioning
confidence: 72%
“…Thus, although the rational design of molecules for biological and pharmaceutical applications is rather well established, only few works predict the complete self-assembly of soft materials using computational tools. 30,31,60,61 Experimental observations presented in this work for small work reflects not only self-similarity but also that the dendritic assembly occurs through a diffusion limited aggregation mechanism onto a plane (i.e. the surface substrate).…”
Section: Fractal Analysis Of Fmoc-ffff-ofm Dendritic Microarchitecturesmentioning
confidence: 72%
“…24 Alternatively, kinetic Monte Carlo (KMC) simulations have been used to study the supramolecular assembly. [27][28][29] For example, self-organized Frechet dendron's pattern observed by STM was reproduced by Monte Carlo simulations. 28 Molecular-bonding energies could be derived by comparing the KMC simulated pattern and images from STM experiments.…”
Section: Introductionmentioning
confidence: 90%
“…294,380,381,48,102,382,322,383,384 Additionally, a notable study using KMC simulations showed that the conditions for realizing stable molecular networks of a bicomponent system are based on the ratio between the directional and isotropic coupling energies for the molecules. 385 A structural stability diagram was obtained that sets the conditions for disordered, compact and network domains according to the temperature and the strength of the H-bonding and vdW energies. This framework was validated using the melamine- triple H-bonds have been described.…”
Section: Towards Predicting Bicomponent Self-assembly: Simulationsmentioning
confidence: 99%